2020
DOI: 10.1111/joor.12981
|View full text |Cite
|
Sign up to set email alerts
|

Jaw‐neck motor function in the acute stage after whiplash trauma

Abstract: Background Jaw‐neck motor function is affected in the chronic stage following whiplash trauma. It is not known whether motor function is affected also in the early stage after neck trauma. Objectives To determine how jaw and head movement amplitudes and movement cycle times correlate with jaw and neck pain, and neck disability in the acute stage after whiplash trauma. Methods Jaw and head movements during jaw opening‐closing were recorded with an optoelectronic system in 23 cases (4 men, 19 women, 18‐66 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Headaches and neck discomfort have been reported to be the most common presenting symptoms along with TMD after WI [ 51 ]. Some authors showed that these symptoms are significantly worse when TMD is due to WI and are associated with higher neck pain intensity [ 123 ]. Based on 2 case-control studies done on TMD patients, Lee and colleagues [ 108 109 ] reported a significant increase in neck pain and headache in post-WI TMD patients compared to patients with TMD from idiopathic causes or other sorts of trauma TMD associated clinical conditions are summed up in Table 3 [ 118 122 123 124 ].…”
Section: Post Traumatic Craniocervical Disorders Reviewed From a Post...mentioning
confidence: 99%
“…Headaches and neck discomfort have been reported to be the most common presenting symptoms along with TMD after WI [ 51 ]. Some authors showed that these symptoms are significantly worse when TMD is due to WI and are associated with higher neck pain intensity [ 123 ]. Based on 2 case-control studies done on TMD patients, Lee and colleagues [ 108 109 ] reported a significant increase in neck pain and headache in post-WI TMD patients compared to patients with TMD from idiopathic causes or other sorts of trauma TMD associated clinical conditions are summed up in Table 3 [ 118 122 123 124 ].…”
Section: Post Traumatic Craniocervical Disorders Reviewed From a Post...mentioning
confidence: 99%